2013
DOI: 10.1542/peds.2012-3886
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Subspecialty Service Use by Children With Autism

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Racial and ethnic differences exist in age at diagnosis and early access to mental and behavioral health services among children with autism spectrum disorders (ASDs). ASDs are also associated with increased rates of other medical comorbidities that may require specialty care.WHAT THIS STUDY ADDS: Significant racial and ethnic differences in use of specialty care and specialty procedures exist among children with documented ASD. abstract OBJECTIVE: To describe racial differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 32 publications
5
51
0
2
Order By: Relevance
“…A study in adult mental health care found a greater disparity in racial and ethnic minorities' access to psychiatrists compared with other providers, 38 and pediatric studies have concluded that disadvantaged groups less frequently see specialists or use prescription medications. 25,[39][40][41][42][43][44] This study has some limitations. Likewise, the extent of management by providers and the depth of discussion at PCP visits could not be determined.…”
Section: Discussionmentioning
confidence: 95%
“…A study in adult mental health care found a greater disparity in racial and ethnic minorities' access to psychiatrists compared with other providers, 38 and pediatric studies have concluded that disadvantaged groups less frequently see specialists or use prescription medications. 25,[39][40][41][42][43][44] This study has some limitations. Likewise, the extent of management by providers and the depth of discussion at PCP visits could not be determined.…”
Section: Discussionmentioning
confidence: 95%
“…Minority parents have been shown to follow through with referrals to specialists at a lower rate than Caucasian parents (Zuckerman et al 2011), a difference that has also been established in regards to autism referral attendance (Kalb et al 2012). Minority parents may face more socioeconomic, scheduling, and transportation barriers to visit specialists (Broder-Fingert et al 2013;Kalb et al 2012). They may also hold different beliefs about the importance or seriousness of specialty consultations and are more likely to have had prior negative experiences in specialty care (Broder-Fingert et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Minority parents may face more socioeconomic, scheduling, and transportation barriers to visit specialists (Broder-Fingert et al 2013;Kalb et al 2012). They may also hold different beliefs about the importance or seriousness of specialty consultations and are more likely to have had prior negative experiences in specialty care (Broder-Fingert et al 2013). Another possibility is that parents of different backgrounds self-refer for autism diagnosis at disparate rates.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, estudios recientes han sugerido que la variación genética común en la población puede contribuir a TEA en un complejo no mendeliano (50)(51)(52)(53)(54).…”
Section: Genéticaunclassified